HUBUNGAN EFIKASI DIRI DENGAN KUALITAS HIDUP PADA LANSIA PENDERITA DIABETES MELLITUS TIPE II: Array (LPPM STIKes Buleleng, 2019)
Introduction : Elderly is the age that is at high risk of degenerative diseases, one of the diseases experienced by the elderly is diabetes mellitus. Type 2 Diabetes Mellitus is a disease characterized by an increase in normal blood sugar levels due to decreased insulin secretion. Self-efficacy is a belief in the ability of individuals to drive motivation, cognitive abilities, individual expectations of the ability to bind to conduct behaviors that support their health in accordance with the desired goals and expectations. Quality of life is a perception of health and life in an appropriate system of life values, expectations and standards they adhere to. Purpose : This research is to find out the relationship of Self-Efficacy with Quality of Life on Elderly Diabetes Mellitus Type 2 patient at Health Center Kubu I Area. Method : In this research using correlational methode eith crossectional approach, in this research there are 52 respondents have been involve with purposive sampling. Result : From the spearman rank analysis found that p-value = 0,002 <0,05. Conclusion : From that research we conclude that there is a relationship of Self-Efficacy with Quality of Life on Elderly Diabetes Mellitus Type 2 patient at Health Center Kubu I Area .